Hubungan Antara Usia dan Jenis Kelamin Terhadap Angka Kejadian Apendisitis di RSUD Dr. Pirngadi Kota Medan - Zebua, Ribka Febrianti; Butar-Butar, Harry; Sihombing, Yan Pieter (Universitas Methodist Indonesia, 2022)
Background : Appendicitis is an acute inflammation that occurs in the vermiform appendix with several precipitating factors. It was found that age and gender were risk factors for appendicitis. Appendicitis increases in adolescents and adults with an age range of 20-30 years. Objective : This study aims to determine the relationship between risk factors for appendicitis to the incidence of appendicitis in RSUD Dr. Pirngadi Medan City. Method : This type of research uses an analytical observational method, with a cross sectional design. The method of data collection was carried out using secondary data obtained from medical records of patients with appendicitis at Dr. Hospital. Pirngadi Medan City 2020-2021. Result : Based on age, the results of the study obtained that the majority of the research sample had an age of 15-30 years, namely 35 people (61.4%) with a p value of 0.018 which was smaller than 0.05. Based on gender, the majority of the research sample was male, as many as 39 people (68.4%) with p value = 0.013 less than 0.05. Conclusion : Based on the results of the study, it can be concluded that there is a significant relationship between age and gender on the incidence of appendicitis in Dr. Hospital. Pirngadi Medan City.